Studies on the method and its efficiency of extracting Bt toxic protein from Bt transgenic rice - WU Zhi-ping; CHEN Zi-yuan; YU Hong; YE Gong-yin; XU Bu-jing (浙江大学学报. 农业与生命科学版, 2001)
Extractive efficiency of several extractants of Bt toxic protein from Bt transgenic rice was studied by orthogonal experiments. The results showed that the extractants and extracting conditions have similar efficiency for Bt toxic protein and the total proteins of the transgenic rice. The solutions of optimum extracting conditions keep highly insecticidal activity.